1976
DOI: 10.1093/jn/106.5.689
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Dietary Zinc on Lead Toxicity in the Rat

Abstract: An investigation of the influence of dietary zinc (8, 35, 200 ppm) on the toxicity of dietary lead (0, 50, 200 ppm) in the young male rat in a seven week period indicated that as dietary zinc increased, the severity of lead toxicity decreased. Evidence included decreased lead concentration in blood, liver, kidneys, and tibias; decreased excretion of urinary delta-aminolevulinic acid; decreased accumulation of free erythrocyte porphyrins; decreased inhibition of kidney delta-aminolevulinic acid dehydrase activi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
46
0
1

Year Published

1979
1979
2012
2012

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 143 publications
(49 citation statements)
references
References 23 publications
2
46
0
1
Order By: Relevance
“…The role of selenium in lead intoxication has rather been controversial. Cerklewski and Forbes investigated the effect of low and high dietary selenium on toxicity of dietary lead in male rats and suggested that low dietary levels mildly protect against toxic effects of lead, but at high levels it exaggerates the lead toxicity 112) . Enzymatic activity of ALAD and Cytochrome P-450 in liver was normal in rats exposed concomitantly to selenium and lead 113) .…”
Section: Seleniummentioning
confidence: 99%
“…The role of selenium in lead intoxication has rather been controversial. Cerklewski and Forbes investigated the effect of low and high dietary selenium on toxicity of dietary lead in male rats and suggested that low dietary levels mildly protect against toxic effects of lead, but at high levels it exaggerates the lead toxicity 112) . Enzymatic activity of ALAD and Cytochrome P-450 in liver was normal in rats exposed concomitantly to selenium and lead 113) .…”
Section: Seleniummentioning
confidence: 99%
“…[20], phosphorus [8,15], and sulfur [21,22]. The disappearance curves for lead excretion in blood, plasma, hematic cells, and some other soft tissues can be expressed as sums of exponential functions.…”
Section: Zincmentioning
confidence: 99%
“…Cerklewski and Forbes (50) showed that increasing dietary zinc from 8 to 200 ppm in lead-poisoned rats decreased lead concentrations in tissues, urinary excretion of 6-aminolevulinic acid, and inhibition of 8-aminolevulinic acid dehydratase activity in the kidney. This antagonistic effect of zinc on lead was thought to be due to its interference in lead absorption since zinc did not affect urinary lead excretion and injected zinc had no effect on lead toxicity.…”
Section: Zinc and Coppermentioning
confidence: 99%